A revision of Anadolua (Orthoptera: Tettigoniidae: Tettigoniinae) based on morphological and bioacoustic characters: Newly confirmed data suggesting a new synonym and two new species - Şi̇ri̇n, Deniz; Taylan, Mehmet Sait; Sevgi̇li̇, Hasan; Akyildiz, Dilan Hevra; Güngör, Oğuzhan (Zootaxa, 2024)
In the present paper, a number of twelve populations of genus Anadolua have been studied by focusing on their morphological and bioacoustic characters. Both bioacoustics and morphological CDF analyses (especially in males) indicate the existence of two new species (A. bergeri sp. nov. and A. moli sp. nov.) and of a new synonym (A. burri syn. nov. synonymized with A. schwarzi). The description of the two new species and the redescription of A. schwarzi are provided with IUCN categories, suggestions and figures, which would comprehensively illustrate the species representing the Anatolian members of genus Anadolua. Two bioacoustic song types (schwarzi and bergeri) are found for Anadolua according to temporal and spectral parameters data of the male calling song. Also presented are the morphological and bioacoustic keys to species of Anadolua. The distribution modelling methods of the species have been carried out for Anadolua species. It has been concluded that the dramatic decrease occurring in potentially suitable habitats necessitates the development in the near future of some conservation action plans for all species of Anadolua.